Antimicrobial Resistance and Criminal Liability: Negligence Recklessness, and Comparative Legal Responses in the EU and United States - Rizaldy Anggriawan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2026)
The emergence of Antimicrobial Resistance (AMR) is now recognized as a catastrophic global public health threat to all of humanity; primarily as a result of the unregulated use of antibiotics below treatment levels in industrial livestock production. This research analyzes the ability of criminal law to prevent or mitigate AMR that develops from agricultural practices. The study utilizes a comparative analysis of the EU and U.S. regulatory and penal systems to assess whether farm owners or corporations could be subjected to prosecution based upon the criminal offences of negligence, recklessness, or corporate liability for public endangerment. The research reveals that the antibiotic misuse in livestock production has been addressed almost exclusively through administrative enforcement mechanisms with criminal prosecution remaining virtually non-existent in both the EU and U.S. legal systems. However, the overwhelming scientific agreement that there is a correlation between livestock antibiotics and the development of antibiotic-resistant infections in humans affords a basis for establishing the legal foreseeability of future harm. While proving factual causation will be complicated due to the diffuse nature of AMR, the existence of statutes that find individuals and corporations liable for risking catastrophe creates an opening for an expanded view of criminal responsibility for egregious misuse of antibiotics.